Design errors in vital sign charts used in consultant-led maternity units in the United Kingdom. (August 2019) - Isaacs, R.; Smith, G.; Gale-Andrews, L.; Wee, M.; van Teijlingen, E.; Bick, D.; Hundley, V.; ,
Highlights: Obstetric observation charts in the United Kingdom contain poor design features. Common errors are inappropriate use of colour, poor alignment and axes labelling. Design errors render charts difficult to use and could compromise patient safety. An evidence-based, standardised obstetric observation chart is required. The chart should integrate 'human factors' and user experience. Abstract: Background: Paper-based charts remain the principal means of documenting the vital signs of hospitalised pregnant and postnatal women. However, poor chart design may contribute to both incorrect charting of data and clinical responses. We decided to identify design faults that might have an adverse clinical impact. Methods: One hundred and twenty obstetric early warning charts and escalation protocols from consultant-led maternity units in the United Kingdom and the Channel Islands were analysed using an objective and systematic approach. We identified design errors that might impede their successful use (e.g. generate confusion regarding vital sign documentation, hamper the recognition of maternal deterioration, cause a failure of the early warning system or of any clinical response). Results: We found 30% (n=36/120) of charts contained at least one design error with the potential to confuse staff, render the charts difficult to use or compromise patient safety. Amongst the most common areas were inadequate patient identification, poor use of colour, illogical weighting, poor alignment and labelling of axes, and the opportunity for staff to 'game' the escalation. Conclusions: We recommend the urgent development of an evidence-based, standardised obstetric observation chart, which integrates 'human factors' and user experience. It should have a clear layout and style, appropriate colour scheme, correct language and labelling, and the ability for vital signs to be documented accurately and quickly. It should incorporate a suitable early warning score to guide clinical management.